Assessment of a glycated hemoglobin point-of-care analyzer (A1CNow+) in comparison with an immunoturbidimetric method: a diagnostic accuracy study - Aurélie Affret; Luiz Henrique Maciel Griz; Eduarda Ângela Pessoa Cesse; Yuri da Silva Specht; Eduardo Maia Freese de Carvalho; Annick Fontbonne (São Paulo Medical Journal)
CONTEXT AND OBJECTIVE: To monitor glycemic control in diabetic patients, regular measurement of glycated hemoglobin (HbA1c) is recommended, but this can be difficult in remote places without access to laboratories. Portable point-of-care testing devices can prove a useful alternative. Our study aimed to assess the performance of one of them: A1CNow+, from Bayer. DESIGN AND SETTING: Cross-sectional accuracy study conducted at a university hospital in Brazil. METHODS: We made three successive measurements of capillary HbA1c using the A1CNow+ in 55 diabetic volunteers, while the same measurement was made on venous blood using the hospital reference method (Vitros 5,1 FS). We used the Bland-Altman graphical method to assess the A1CNow+ in relation to the Vitros 5,1 FS method. We also evaluated clinical usefulness by calculating the sensitivity and specificity of A1CNow+ for detecting patients with HbA1c lower than 7%, which is the usual limit for good glycemic control. RESULTS: The coefficient of variation between repeat testing for the A1CNow+ was 3.6%. The mean difference between A1CNow+ and Vitros 5,1 FS was +0.67% (95% confidence interval, CI: +0.52 to +0.81). The agreement limits of our Bland-Altman graph were -0.45 (95% CI: -0.71 to -0.19) and +1.82 (95% CI: +1.52 to +2.05). The sensitivity and specificity in relation to the 7% limit were respectively 100% and 67.7%. CONCLUSIONS: Although the A1CNow+ had good sensitivity, its accuracy was insufficient for use as a replacement for laboratory measurements of HbA1c, for glycemic control monitoring in diabetic patients.